Kasus Ujaran Kebencian dalam Berita Surat Kabar di Hindia Belanda - Nugraha, Fajar Muhammad; de Archellie, Reynaldo; Clement, Cresentia Carra Nethania (UI Scholars Hub, 2020)
This article is a preliminary study that explores past events of the Dutch East Indies colonial government, specifically describing criminal cases of hate speech or haatzaai depicted in newspaper news between 1879 and 1942. The Dutch East Indies colonial government controlled freedom of thought, expression, and politics of the native population by using the legal instruments Wetboek van Strafrecht voor Nederlandsch Indie, especially articles 154, 155, 156, and 157. These four articles are known as haatzaai artikelen. This regulation was published and enforced in the Dutch East Indies in 1918. This article uses twenty-eight newspaper news articles published in ten cities on the islands of Java and Sumatra as the primary sources. This is research that uses historical methods by gathering primary and secondary sources in the National Archives of the Republic of Indonesia (Jakarta), the National Library of the Republic of Indonesia (Jakarta), and the Constitutional Institution voor Taal-, Land- en Volkenkunde (KITLV) (Jakarta). This article concludes that based on the news articles found, haatzaai artikelen, as a repressive legal product, is not only used by the colonial government to control people’s behavior but also used by fellow members of the community of East Indies to quarrel with each other in many cases of hatred, incitement, and defamation.